2013
DOI: 10.1016/j.bbmt.2012.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Fractal Organization of the Human T Cell Repertoire in Health and after Stem Cell Transplantation

Abstract: T cell repertoire diversity is generated in part by recombination of variable (V), diversity (D), and joining (J) segments in the T cell receptor β (TCR) locus. T cell clonal frequency distribution determined by high-throughput sequencing of TCR β in 10 stem cell transplantation (SCT) donors revealed a fractal, self-similar frequency distribution of unique TCR bearing clones with respect to V, D, and J segment usage in the T cell repertoire of these individuals. Further, ranking of T cell clones by frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(85 citation statements)
references
References 25 publications
(28 reference statements)
3
82
0
Order By: Relevance
“…As previously described, CD3þ cells were isolated from SCT donor samples and cDNA synthesized from these cells [10]. The cDNA was then sent to Adaptive Biotechnologies (Seattle, WA) for high-throughput sequencing of the TCR b CDR3 region using the ImmunoSEQ assay.…”
Section: T-cell Clonal Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…As previously described, CD3þ cells were isolated from SCT donor samples and cDNA synthesized from these cells [10]. The cDNA was then sent to Adaptive Biotechnologies (Seattle, WA) for high-throughput sequencing of the TCR b CDR3 region using the ImmunoSEQ assay.…”
Section: T-cell Clonal Frequencymentioning
confidence: 99%
“…Repetitive or cyclic phenomenon too may be described mathematically using trigonometric ratios. It is to be noted that the universal constants p and e have a role in calculating the trigonometric ratios and FD, and have been identified in analysis of the T-cell repertoire [10], which would imply that the TCR locus may be arranged in conformity with these constants, and demonstrate self-similarity as well as periodic characteristics. An inspection of the known sequence of the TCR loci with attention to V and J gene segment size and spacing supports this notion.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies, such as next-generation sequencing (NGS), offer the opportunity to assess the TCR repertoire on an unprecedented level. So far, most TCR sequencing in the setting of allogeneic transplantation has focused on assessment of the TCR-b chain [5][6][7]. A recent report assessed the TCR-b repertoire of CMV-specific T cells by NGS and demonstrated a high prevalance of dominant clonotypes in kidney allograft recipients [8].…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with previous reports that patients with GVHD after HSCT and stem cell transplant recipients had a significantly smaller and restricted T-cell repertoire. 7,14 We found that there was little similarity among the TRB repertoires of different healthy individuals with Bhattacharyya coefficients <0.10, and there was even less similarity among the TRB repertoires of different patients with GVHD with Bhattacharyya coefficients typically <0.08 (data not shown). The top 100 CDR3 sequences and their V/D/J gene rearrangements in healthy individuals and patients with GVHD are shown in Supplemental Tables S2 and S3.…”
Section: Trb Repertoire By Ngsmentioning
confidence: 79%
“…These results are consistent with previous reports that patients with GVHD after HSCT and stem cell transplant recipients have a significantly smaller and restricted T-cell repertoire. 7,14 NGS technology has emerged as a tool to quantify TCR repertoires that is quickly moving from a research tool to commercial and clinical testing for assessment of clonality and assessment of immune interventions. Defining standards and limitations of library preparation, sequencing and data analysis for detection of TCR repertoires with NGS is a recognized need in the field.…”
Section: à5mentioning
confidence: 99%